How a distractor influences fixations during the exploration of natural scenes - Hélène Devillez; Anne Guérin-Dugué; Nathalie Guyader (Journal of Eye Movement Research)
The distractor effect is a well-established means of studying different aspects of fixation pro-gramming during the exploration of visual scenes. In this study, we present a task-irrelevant distractor to participants during the free exploration of natural scenes. We investigate the con-trol and programming of fixations by analyzing fixation durations and locations, and the link between the two. We also propose a simple mixture model evaluated using the Expectation-Maximization algorithm to test the distractor effect on fixation locations, including fixations which did not land on the distractor. The model allows us to quantify the influence of a visual distractor on fixation location relative to scene saliency for all fixations, at distractor onset and during all subsequent exploration. The distractor effect is not just limited to the current fixa-tion, it continues to influence fixations during subsequent exploration. An abrupt change in the stimulus not only increases the duration of the current fixation, it also influences the location of the fixation which occurs immediately afterwards and to some extent, in function of the length of the change, the duration and location of any subsequent fixations. Overall, results from the eye movement analysis and the statistical model suggest that fixation durations and locations are both controlled by direct and indirect mechanisms.